2012
DOI: 10.1258/ijsa.2011.011276
|View full text |Cite
|
Sign up to set email alerts
|

Calvarial syphilis in an HIV-positive man

Abstract: Bone involvement in secondary and tertiary syphilis is a well-documented but unusual phenomenon. We report the case of an atypical presentation of secondary syphilis in a 25-year-old HIV-positive man who has sex with men. He presented initially with headaches and an unusual calvarial swelling. The skull findings were consistent with osteitis and he later developed systemic symptoms. Treponema pallidum serology was positive and the lesions and systemic symptoms resolved completely after administration of approp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 6 publications
(9 reference statements)
0
6
0
Order By: Relevance
“…Until now cortical osteoporosis has not been described in conjunction with syphilis. This finding also underlines the technical advantage of microcomputed tomography since the identification of cortical osteoporosis is beyond the resolution of conventional computed tomography or magnetic resonance imaging [ 32 , 36 ]. Although cortical porosity is likely not specific for syphilis, this finding in conjunction with other features observed in our study could be helpful for the differential diagnosis of pathologies observed in human skeletal remains.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Until now cortical osteoporosis has not been described in conjunction with syphilis. This finding also underlines the technical advantage of microcomputed tomography since the identification of cortical osteoporosis is beyond the resolution of conventional computed tomography or magnetic resonance imaging [ 32 , 36 ]. Although cortical porosity is likely not specific for syphilis, this finding in conjunction with other features observed in our study could be helpful for the differential diagnosis of pathologies observed in human skeletal remains.…”
Section: Discussionmentioning
confidence: 85%
“…[ 31 ] showed that Tp92 homologs stimulated various factors involved in inflammation and osteoclastogenesis, such as IL-1ß, TNF-alpha, IL‑6 and PGE 2. Remarkably, several contemporary case reports impressively underline the massive bone destructive potential of (untreated) syphilis [ 32 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…A common theme in all of these cases was secondary syphilis being diagnosed as osteitic lesions in MSM patients with well controlled HIV infection. 4,5,6,7 Some have hypothesized that HIV-infected patients may present with more aggressive and often rarely described manifestations of syphilis. 8 In one such case report, it was suggested that syphilitic osteitis may be more aggressive in HIV-infected patients due to impaired cell-mediated immunity, with authors noting a very large number of spirochetes seen in their patient’s bone biopsies.…”
Section: Discussionmentioning
confidence: 99%
“…Although only one report about this issue has been documented in Korea, 6 other similar reports are available from other countries. [7][8][9][10][11][12][13][14][15][16] Bone pain is the most common complaint, which is aggravated during the night and upon exposure to heat and pressure. Involvement of the skull can lead to headache, usually in the frontotemporal area.…”
Section: Bone Involvementmentioning
confidence: 99%
“…Involvement of the skull can lead to headache, usually in the frontotemporal area. [6][7][8][9][10][11][12][13][14][15][16] Prompt resolution of bone pain after penicillin therapy is evidence of a syphilitic cause for the bone lesions. A diagnosis of early syphilis is suspected based on the mucocutaneous findings in 76% of patients.…”
Section: Bone Involvementmentioning
confidence: 99%